(untitled) (Journal of Bio-Science, 2023)
Congenital heart disease (CHD) is a congenital defect affecting the structure of the heart. Early detection can be done by auscultating the murmur and this could help to diagnosis the disease. This study was aimed to detect CHD by rapid evaluation of clinical features, findings and cardiac auscultation which will help to customize the future management plan in each CHD child and reduce the progression of complications and financial burden associated with CHD on this region over time. This descriptive cross-sectional study was conducted on children hospitalized to the paediatric department. A systematic sampling technique was implemented. Total 3978 children were taken during the study period among them 54 were detected as CHD. Total 3978 children under 10 years were examined during the study. Among them-murmur with CHD was found in 54 (1.36%) cases and it was found that 30 (55.6%) were male and most (53.7%) of them from rural area came from 42.6% middle socio-economic group. It was revealed that, among the study cases 40.70% had ventricular septal defect (VSD), 63% had rapid breathing regarding clinical presentation. Regarding clinical findings among the study cases 33 (61.10%) had chest retractions. Among 54 murmur positive cases 29 (53.70%) had pansystolic murmur which help to assess regarding CHD before completing echo. Congenital heart disease, especially in the newborn era, is a pediatric cardiology emergency due to the high morbidity and mortality rates. This research could aid in the early diagnosis of CHD and save the lives of youngsters. J Bio-Sci. 30(1): 115-121, 2022 (June)